Specyfika nazewnictwa środków kosmetycznych: aspekt strukturalny = The naming specificity of the cosmetics: the structural aspect - Galicka, Jelizaweta (Zielona Góra: Uniwersytet Zielonogórski, Instytut Filologii Polskiej)
The article is connected with the problem of naming the perfume-cosmetic goods in the aspect of using somatisms as components of names. The problem of perfumes and cosmetics nomination is considered in the descriptive paradigm of structures and basic names components due to the perception of somatisms' functions. A few basic constituents in the structure of perfume and make-up names have been identified.
Keywords: somatyzm; anatomiczno-topograficzny wskaźnik; nominacja wyrobów perfumeryjno-kosmetycznych; wskaźnik semantyczny; somatism; anatomic-topographical marker; nomination of perfume-cosmetic goods; semantic indicator